Development and Validation of an Instrument to Assess Social Work Students' Perceptions, Knowledge, and Attitudes About Human Trafficking Questionnaire (PKA-HTQ): An Exploratory Study. (September 2017) - Nsonwu, Maura Busch; Welch-Brewer, Chiquitia; Heffron, Laurie Cook; Lemke, Melinda A.; Busch-Armendariz, Noel; Sulley, Caitlin; Cook, Sharon Warren; Lewis, Mary; Watson, Elizabeth; Moore, Wayne; Li, Jilan
Objective: This study sought to develop and evaluate the psychometric properties of a tool designed to assess social work students' knowledge of and perceptions and attitudes toward human trafficking. To achieve this aim, the Perceptions, Knowledge, and Attitudes toward Human Trafficking Questionnaire (PKA-HTQ) was developed and its psychometric properties were evaluated. Specifically, the factor structure and the internal consistency of the PKA-HTQ were evaluated. Methods: Exploratory factor analysis (EFA) and a replication EFA were conducted on two independent samples of university students, an initial validation ( n = 325), and cross-validation ( n = 212) sample. Findings: The EFA revealed a three-factor structure, that is, self-appraisal of knowledge/skills (α = .89), worldview (α =.78), and help-seeking behavior (α =.66); this three-factor structure was supported by replication EFA. Conclusion: The PKA-HTQ questionnaire shows promise as a meaningful, potentially reliable and valid measure.